Improving educational quality through enhancing community participation: results from a randomized field experiment in Indonesia - Pradhan, M.; Suryadarma, D; Beatty, A; Wong, M; Gaduh, A; Alisjahbana, A; Artha, R.P. (American Economic Association, 2014)
Education ministries worldwide have promoted community engagement through school committees. This paper presents results from a large field experiment testing alternative approaches to strengthen school committees in public schools in Indonesia. Two novel treatments focus on institutional reforms. First, some schools were randomly assigned to implement elections of school committee members. Another treatment facilitated joint planning meetings between the school committee and the village council (linkage). Two more common treatments, grants and training, provided resources to existing school committees. We find that institutional reforms, in particular linkage and elections combined with linkage, are most cost-effective at improving learning. (JEL H52, I21, I25, I28, O15)